Pengaruh Peer Influence, Pengelolaan Pendapatan, dan Literasi Keuangan Terhadap Intensitas Bermain Judi Online di Kabupaten Ngawi - Intan Wulan Prasetiyaningsih; Novita Erliana Sari; Maretha Berlianantiya (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The phenomenon of online gambling among adolescents in Ngawi Regency has shown an alarming increase. Field observations reveal that many teenagers desperately sell family assets and use their school allowance to obtain gambling deposit capital. This risky behavior is strongly driven by intense peer influence (the "word-of-mouth" system) and the ease of digital access amid economic pressure, coupled with a lack of financial literacy and healthy income management. This study aims to analyze the effect of peer influence, income management, and financial literacy, both partially and simultaneously, on the intensity of online gambling among adolescents in Ngawi Regency. This study uses a quantitative approach with a causal-associative design. The research population consists of male adolescents aged 13–19 residing in Ngawi Regency. The analyzed sample amounted to 98 respondents selected using a random sampling technique, with the inclusion criteria of having experience playing online gambling within the last six months. The source of data used is primary data collected through a survey method using a structured questionnaire with a 4-point Likert scale. Data analysis techniques include classical assumption tests, multiple linear regression, and hypothesis testing (partial t-test, simultaneous F-test, and coefficient of determination) using SPSS version 24. The test results show that partially, peer influence has a positive and significant effect on the intensity of playing online gambling (Sig. 0.000 < 0.05). Conversely, income management (Sig. 0.898 > 0.05) and financial literacy (Sig. 0.698 > 0.05) proved to have no significant effect partially. Nevertheless, simultaneously, peer influence, income management, and financial literacy have a significant effect on the intensity of online gambling (Sig. 0.000 < 0.05). The coefficient of determination reached 92.4%, which means these three variables have a dominant contribution in explaining the variation in adolescent gambling intensity, while the remaining 7.6% is explained by factors outside the study.